2017
DOI: 10.1002/app.45141
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and properties of thermosets based on the cocuring of an acetylene‐terminated liquid‐crystal and silicon‐containing arylacetylene oligomer

Abstract: A thermotropic acetylene-terminated liquid-crystal monomer, 2-methyl-1,4-phenylene bis(4-ethynylbenzoate) (MPBE), was prepared and used as a modification composition to react and cocure with a silicon-containing arylacetylene (PSA) oligomer for improving PSA resin. The curing behavior of the PSA-MPBE resins were characterized by differential scanning calorimetry and Fourier transform infrared spectroscopy. The microstructure and morphology of the PSA-MPBE resins were investigated by scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…(4) Adding thermoplastic liquid crystalline polymers: Han et al . prepared a thermotropic acetylene‐terminated liquid‐crystal monomer, 2‐methyl‐1, 4‐phenylene bis (4‐ethynylbenzoate) (MPBE) and used it as a modification composition to react and co‐cure with a silicon‐containing arylacetylene (PSA) oligomer for improving PSA resin . The results indicated that MPBE and PSA could copolymerize to fix the mesogenic domain in the crosslinked network and form a homogeneous‐phase sea‐island structure that improved the rigidity and toughness of the materials.…”
Section: Trend and Future Explorationmentioning
confidence: 99%
“…(4) Adding thermoplastic liquid crystalline polymers: Han et al . prepared a thermotropic acetylene‐terminated liquid‐crystal monomer, 2‐methyl‐1, 4‐phenylene bis (4‐ethynylbenzoate) (MPBE) and used it as a modification composition to react and co‐cure with a silicon‐containing arylacetylene (PSA) oligomer for improving PSA resin . The results indicated that MPBE and PSA could copolymerize to fix the mesogenic domain in the crosslinked network and form a homogeneous‐phase sea‐island structure that improved the rigidity and toughness of the materials.…”
Section: Trend and Future Explorationmentioning
confidence: 99%
“…Thus, stability in various environments, except under mechanical stimuli, is highly desirable for the development of N* LC elastomers with highly sensitive mechano-optical response behavior. In recent decades, N* LC network polymers with high cross-linking densities have attracted practical interest because of their thermally stable optical properties [35][36][37]. However, dense cross-linking is not appropriate for mechano-optical sensors because of the associated high glass transition temperature and low flexibility [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…However, the thermal curing temperature of PSA resins is usually higher than 200 °C, which limits their further applications 19–23 . In addition to designing new chemical structures, some efforts have been devoted to decreasing the curing temperature of PSAs 24–27 . For example, introducing catalysts can decrease the curing temperature of PSA resins 25 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the remaining metal ions could affect the dielectric properties of the resulting polymers. In some cases, mixing with other polymers decreases the curing temperature of PSA resins 26 . However, this usually lowers the heat resistance of the resins.…”
Section: Introductionmentioning
confidence: 99%